Civil and reform forces in Montenegro towards the war against Bosnia and Herzegovina - Dr. sc. Nada TOMOVIĆ (Historijski pogledi, 2023)
The aim of this paper is to review, based on the available sources, the role of democratic and civic forces in Montenegro which were against sending Montenegrin reservists to war in Croatia and Bosnia and Herzegovina. However, this topic can be analyzed from different aspects, social, political, national, sociological, international, historical, etc. The objective of this study is to highlight the most notable individuals, groups of intellectuals, political organizations, and other associations that advocated for anti-war policies, their treatment by the authorities, and the humiliation and persecution they suffered for their views, all within the social and political context of the time. One of the challenges in writing this paper was the lack of access to archival materials, which are still not available. Consequently, this study relied heavily on the excerpts of the only independent publication in Montenegro at the time, Monitor, and the newspaper Liberal, the publications of the Liberal Alliance, as they reported on anti-war protests, interviews with prominent intellectuals, forms of resistance of various organizations and parties. Although the press is a secondary source, it provided valuable testimony in the absence of archival material. Until recently, in Montenegro almost nothing has been written about the 90’s wars. What are the reasons? This can be the subject of a separate work. But we must state that this is no longer the case. The sources from a very valuable monograph were used in this paper, the monograph in which the facts about the new Montenegrin history were revealed to the scientific and wider general public - the facts which were kept as a secret until now. However, the participation of Montenegrin reservists both in the war in Bosnia and Herzegovina and in Croatia cannot be justified by any facts. Nevertheless, it should be kept in mind that at that time, Montenegro was a member of a two-member federation (Serbia and Montenegro) and was involved in the war following the instructions of the Supreme Military Command and the political leadership in Belgrade. Unfortunately, the Montenegrin leadership blindly followed that politic. The ruling elite of the Montenegrin politics in the conjunction with the military elite deceived the people by referring to the “heroic past”, tradition, patriarchal norms which dictated that it was a shame not to respond to a military call for “the defense of the homeland”. Progressive civic forces in Montenegrin society did not think this way, and a broad anti-war movement was formed, although it remained in the shadow of those who held power in their hands. Nevertheless, the actions of civic and reformist forces in Montenegro in the 1990s have left an indelible mark on modern Montenegrin history. In addition to trying to promote reason and help the voice of justice to win, they simultaneously fought for the restoration of state independence. It was a difficult and exhausting struggle, which is still not acknowledged properly. The committed mistakes, if they can even be called like that, for that is too mild a word, were accepted late by those who were at the head of political top of Montenegro. Many of the most vocal opponents of Montenegro’s participation in the war affected former Yugoslav republics and bearers of the fight for the renewal of the independence, like Slavko Perović. were totally forgotten.